A 3D cross-linked graphene-based honeycomb carbon composite with excellent confinement effect of organic cathode material for lithium-ion batteries. (February 2020) - Sui, Dong; Xu, Lingqun; Zhang, Hongtao; Sun, Zhenhe; Kan, Bin; Ma, Yanfeng; Chen, Yongsheng
Abstract: Organic cathode materials are drawing increasing attention in lithium-ion battery for their abundance, environmental friendliness, high specific capacity, low cost, and flexibility. But their application has been hindered by poor electrochemical performance because of inherent low conductivity and high solubility in the polar organic electrolyte. Herein, an organic-inorganic composite by impregnating electrochemically active 4, 8-dihydrobenzo [1, 2-b:4, 5-b'] dithiophene-4, 8-dione (BDT) into the pores of 3D cross-linked graphene-based honeycomb carbon (3DGraphene) has been prepared, which not only offers a highly conductive framework with plenty of interconnected pores from the 3D graphene network, but also simultaneously overcomes the two typical drawbacks of organic cathode materials. The excellent confinement effect of the nanopores and the strong π-π interaction between BDT and 3DGraphene largely avoid the dissolution of BDT in the electrolyte. Therefore, the obtained BDT/3DGraphene composite shows a much improved good rate capability (more than 100 mAh g −1 at 4.0C vs less than 50 mAh g −1 for BDT) and cycling stability (about 80% capacity retention at 0.5C while only ∼14% for BDT for 200 cycles), as well as high reversible specific capacity (over 210 mAh g −1 ). Graphical abstract: Image 1